EVALUASI NON-PHYSICAL WASTE DENGAN LEAN CONSTRUCTION PADA PROYEK GEDUNG SANGGALA - Marselino Gamaliel Tamallo; Afrizal Nursin (Prokons: Jurnal Teknik Sipil, 2020)
Abstract The construction industry faces many challenges with problems related to construction waste as it takes up time and effort without adding value to clients. A concept in project management, namely lean construction, has the main focus of minimizing waste and providing added value to a construction project. The purpose of this study was to know the existence of non-physical waste, its causative factors, and how lean construction can be implemented to minimize non-physical waste in earthworks, foundations and basement 2 of the Sanggala Hotel and Office Building Project. The study was carried out by observation, document study, and questionnaires to identify non-physical waste. This study showed that the non-physical waste that most often occurs in related project was equipment breakdown frequently with a weight of 0.086. Meanwhile, the non-physical waste variable that has the greatest impact on causing time overrun on the project was delayed schedule with a weight of 0.080. Equipment breakdown frequently is influenced dominantly by the equipment shortage. Delayed schedule is influenced dominantly by licensing problems. In general, lean construction approaches such as Construction Meetings, Preventive And Predictive Maintenance, and Fail-Safe For Quality And Safety can be applied by contractors to minimize non-physical waste that was dominant in the project. Keywords: Lean Construction, Non-Physical Waste, Waste